Thermal modelling and control of building temperature - Lee, William Chu Ching. (University Malaysia Sarawak (UNIMAS), 1998)
This thesis studied computer simulation of thermal model and demonstrated the application of computer simulation to solve close loop control system design problem. A thermal model is a mathematical model that is able to estimate the temperature and energy demand of a building. Control system produces an output for a given input and a close loop control system has a feedback path which feed back the output signal to the controller.